БУККАЛЬНЫЙ ЭПИТЕЛИЙ КАК ОБЪЕКТ ДЛЯ ИЗУЧЕНИЯ СИГНАЛЬНЫХ МЕХАНИЗМОВ «программирования» ожирения у детей - Кветной, Игорь Моисеевич; Полякова, Виктория Олеговна; Крылова, Юлия Сергеевна; Евсюкова, Инна Ивановна; Дробинцева, Анна Олеговна; Гашимова, Улдуз Файзиевна; Клейменова, Татьяна Сергеевна (Медицина: теория и практика, 2020)